Classification by broad economic categories : defined in terms of SITC, rev. 3 (UN New YorkUS, 1986)
Outlines the broad economic categories (BEC) used for summarization of data on international trade. The main and sub categories describe primary and processed commodities. For each of the BEC's describes the corresponding SITC rev. 3 codes.
IDS